EFFECT OF ORGANIZATIONAL COMMITMENT AND COMPENSATION ON TURNOVER INTENTION OF PT INFOMEDIA NUSANTARA - Bahtiar Herman; Muh Abduh Anwar; Aksal Mursalat (Universitas Islam Lamongan, 2022)
This study aims to examine and analyze the Effect Of Organizational Commitment And Compensation On Employee Turn Over Intention. This study uses a quantitative approach. The object under study is an employee who works at the office of PT Infomedia Nusantara. The data in this study were obtained by survey methods and research instruments in the form of a questionnaire. The research sample was 120 people who were selected by the census sampling method. Data were analyzed by multiple regression method using SPSS program. The results of this study indicate that organizational commitment and compensation influence the Turnover Intention of PT Infomedia Nusantara.